Institutional change and organisational resistance to gender equality in higher education: An Irish case study - Margaret Hodgins; Pat O'Connor; Lucy-Ann Buckley (Administrative Sciences, 2022)
Attempts to transform the gendered structures and cultures of higher education institutions have had limited success. This article focuses on one Irish university (pseudonym University A) where gender inequality was a major concern culminating in high-profile litigation. Using a feminist institutional approach, it asks: (1) What changes and interventions were introduced in the context of a favorable national policy environment and local grassroots support? and (2) how were these interventions perceived by staff? The methodology draws, firstly on the authors' personal knowledge of the local context; secondly, on an analysis of University A's key gender equality-related actions and documents; and thirdly, on a thematic analysis of qualitative data from 129 respondents in an online survey. Positive changes are identified, as is institutional resistance, reflected in low ambitions and focus on individualistic solutions. In the qualitative data, resistance involving denial; assertions that the problem is solved; the importance of meritocracy, and a focus on "fixing the women" (and the men) were identified. Acceptance of gender equality as an organisational issue was reflected in criticism of the interventions as tokenistic window dressing; not impacting on the culture and "not going far enough". The implications for effectively addressing gender inequality are discussed.
Keywords: 350; gender inequality; higher education; Irish; organisational resistance; tokenistic